STUDY BETWEEN OIL CONTENT SEAWATER AND DIATOMS ABUNDANCE IN AIR HITAM STRAIT MERANTI ISLANDS REGENCY RIAU PROVINCE - Syukri Fajar; Irvina Nurrachmi; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted on February until March 2017 with a goal todetermine the relationship between the oil content and the abundance of diatoms,in Air Hitam Strait Meranti Islands Regency Riau Province. The survey methodwere conducted in four stations, in which three sampling. It revealed t hat the oilcontent of water ranged (0.2687 to 0.7889 ppm) and diatom abundance between(116 to 287 cells/l) which contain of 7 species. Of research results, the oilcontent in the sea water with an abundance of diatoms have a strong relation withthe value of the correlation coefficient r = 0.727, regression equation appeared y= 337.04 – 233.71 x with a coefficient of determination (R2) = 0, 5291 and thevalue of the Sig < 0.05. It was suggested that increasing oil content will decreasethe abundance of diatoms in the Air Hitam Strait.Key Words: abundance, diatoms, oil content